What is Transfer Learning in Medical AI? Bridging the Data Gap for Advanced Diagnostics - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Keywords: Transfer Learning, Medical AI, Deep Learning, Medical Imaging, Digital Health, AI Diagnostics, Healthcare Technology
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care